The retinoid signaling pathway inhibits hematopoiesis and uncouples from the Hox genes during hematopoietic development - Szatmari, Istvan (2010)
Retinoic acid (RA) is a well established inducer of Hox genes during development of neurectoderm, however effects of RA on Hox expression are poorly defined in mesoderm and not defined in the hematopoietic compartment. Both Hox genes and retinoid signaling have been suggested to modulate HSC self-renewal, supporting the notion that RA signaling might drive HSC self-renewal through Hox gene induction. Here we investigate this possibility by comprehensively evaluating Hox gene expression using mouse embryonic stem (ES) cells differentiated in vitro. In unspecified mesoderm, we find that RA coordinately upregulates anterior 3’ Hox genes from clusters A, B, and C, and downregulates posterior 5’ Hox genes from clusters A-D. However, hematopoietic development of mesoderm was inhibited by RA, and we find further that retinoids are entirely dispensable for hematopoiesis in vitro. More surprisingly, in fully specified hematopoietic progenitors, Hox genes are refractory to regulation by RA, although other RA targets are normally regulated. Pulses of RA exposure demonstrate that the Hox complexes are decoupled from RA regulation progressively in lateral plate mesoderm as it undergoes hematopoietic specification. Thus, Hox genes are targets of the RA pathway only in selected cell types, and are clearly not regulated by RA in the earliest hematopoietic progenitors. We propose that the developmental uncoupling of the Hox complexes protects the Hox code from potential RA signaling centers as hematopoietic stem cells migrate or circulate during development.